Transformation of the Strategic Culture of Ukraine under the Influence of the Russian Threat - Olga Reznikova; Oleksandr Hryhorenko; Viacheslav Myronenko (Politologija)
The article focuses on strategic culture as an analytical tool that provides a deeper understanding of a state’s behavior and its strategic choice to use force, whether for aggression or self-defense, using Russia’s full-scale war against Ukraine as a case study. While strategic culture is generally resistant to change, we identified shifts in Ukraine’s strategic culture in response to external shocks in 2014 and 2022. This was based on an analysis of military-political behavior patterns, components, and manifestations of strategic culture, as reflected in state strategies on national security and defense, as well as in other relevant documents and texts. We argue that Russia’s aggressive military-political behavior, shaped by Soviet-imperial revanchist sentiments, has become an existential threat to Ukraine. This study contributes to a better understanding of why some conflict resolution measures and strategies have proven ineffective in addressing the ongoing Russian war.